2016
DOI: 10.1021/acs.inorgchem.6b01193
|View full text |Cite
|
Sign up to set email alerts
|

Ambient-Temperature Spin-State Switching Achieved by Protonation of the Amino Group in [Fe(H2Bpz2)2(bipy-NH2)]

Abstract: Magnetism of a complex [Fe(H2Bpz2)2(bipy-NH2)] (H2Bpz2 = dihydrobis(1-pyrazolyl)borate, bipy-NH2 = 4,4'-diamino-2,2'-bipyridine) has been altered from paramagnetic to spin-crossover (SCO) behavior, through protonation of one amino group of bipy-NH2 with CF3SO3H. Complete SCO transition, both in solid state and in solution, occurs at ambient temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 55 publications
4
55
0
3
Order By: Relevance
“…between the highest d π -orbital and the d z 2 -orbital, while the series 2 to 4 bearing different ester group turned out to reveal a relatively large energy splitting of ∆ and stronger π-acceptor properties, which stabilized the LS state 16 ( Figures S8-S12).…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…between the highest d π -orbital and the d z 2 -orbital, while the series 2 to 4 bearing different ester group turned out to reveal a relatively large energy splitting of ∆ and stronger π-acceptor properties, which stabilized the LS state 16 ( Figures S8-S12).…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…Different types of spin crossover curves: Left to right-abrupt and complete, gradual and complete, stepped and complete, abrupt and complete with hysteresis, and gradual and incomplete. Sustainability 2020, 12, 2512 3 of 50When the aim is to analyze the behavior of isolated molecules, SCO has been either studied in solution [38][39][40][41][42][43] or by depositing them on supports [44][45][46][47][48][49]. In solution, the distribution of spin states is assigned using a Boltzmann distribution, and a spin equilibrium is expected at different temperatures.…”
mentioning
confidence: 99%
“…Most recently, Lehn and co‐workers showed that the SCO behavior of a polynuclear {Fe 4 } grid‐type complex can be modified in response to pH by using protic ditopic ligands . And while mononuclear Fe II ‐complexes which reversibly respond to protonation/deprotonation are known, these systems can be switched between just two discrete states . Here, we describe a novel ligand design strategy employing an asymmetric Brønsted ligand (Scheme ) that can be used to isolate a mononuclear Fe‐complex with five independently accessible physical states.…”
Section: Figurementioning
confidence: 96%